FACTORS RELATED TO MATERNAL DEATH AND INFANT DEATH IN INDONESIA - Helvy Yunida (Bajang Institute, 2022)
Background: Maternal Mortality Rate and Infant Mortality Rate in Indonesia are still high. According to Supas (2015) that the MMR is 305, it means that there are 305 maternal deaths caused by pregnancy, childbirth until 42 days after giving birth. 1. The main causes of maternal death due to hemorrhage, pre-eclampsia and comorbidities. Based on the results of the Indonesian Demographic and Health Survey (IDHS), infant mortality in 2017 was 24/1,000 KH.3 The causes of infant mortality: LBW, Asphyxia and Congenital Disorders. LBW and prematurity are still the main causes of infant mortality (38.8/1000 KH). Research Objectives: To determine the factors associated with the incidence of AKI and IMR in Indonesia. The research method used is by using secondary data, namely literature study (library study) by collecting all references or reading materials such as printed books, rule books, Google Scholar and Mendeley looking for journals with the same title or related ones. Discussion: factors related to maternal mortality and infant mortality are complications of childbirth, history of anemia, low birth weight, asphyxia, congenital abnormalities, and premature birth, ANC examination, maternal employment status, health costs, maternal age, maternal knowledge , Mother's education, Parity, pregnancy distance, maternal weight, maternal upper arm circumference, history of maternal chronic disease, bleeding, hypertension, birth attendant, family participating in family planning, delivery assistance from non-health facilities, infant not receiving complete basic immunization, utilization (ASI) exclusive, monitoring the growth of toddlers. Conclusion: there are factors related to maternal mortality and infant mortality in Indonesia either directly or indirectly